Upaya Penatalaksanaan Intoleransi Aktivitas Pada Pasien Congestive Heart Failure - Ardianta, Dicky; , Arief Wahyudi Jadmiko, S.Kep., Ns., M.Kep (2017)
Background: The incidence of heart failure in Indonesia has increased quite significantly from year to year. In addition, the disease of heart failure causes the appearance of symptoms such as chest pain. Chest pain arises because the oxygen supply to the myocardium decreases, this will have an impact on the death of heart cells. If the pain is left alone, the severity of the pain becomes elevated. In the end will cause neurological shock in the person. Objective: Describe the management of activity intolerance in patients with heart failure. Method: Descriptive method with case study approach at inpatient ward of a hospital on 11-13 February 2017. Data collection by observation, physical examination, medical record, interview, documentation study from journal and book and supported by journals. Result: Patient showed decreased shortness of breath and no distress activity after action. There are influences of deep breathing relaxation, health education to the family, scheduling activities, and resting. Conclusion: The act of deep breathing relaxation, warm compresses and progressive relaxation effectively decreases chest pain. Suggestions: Action Relaxation of deep breath, warm compresses and progressive relaxation can be an input in self-care nursing actions to deal with pain.